Strength and conditioning. A concise introduction - Cissik, J. (Routledge, 2012)
Strength and Conditioning offers a concise but comprehensive overview of training for athletic performance. Introducing essential theory and practical techniques in all of the core areas of athletic training, the book clearly demonstrates how to apply fundamental principles in putting together effective real-world training programs.